Vascular deficits contributing to skeletal fragility in type 1 diabetes - Draghici, Adina E.; Zahedi, Bita; Taylor, J. Andrew; Bouxsein, Mary L.; Yu, Elaine W. (Frontiers in Clinical Diabetes and Healthcare, 2023)
Over 1-million Americans have T1D and improvements in diabetes management have expanded the lifespan of adults with T1D. Older adults with diabetes are more susceptible to aging comorbidities, including both vascular disease and osteoporosis. Indeed, those with T1D have a 2-to 3-fold higher risk of fracture. Recently, diabetes-related vascular deficits have emerged as potential risks factors for impaired bone blood flow and poor bone health. Indeed, microvascular disease (MVD) has been linked to worse bone microarchitecture in those with T1D compared to their counterparts without MVD. The association between MVD and compromised bone microarchitecture indicates the potential direct deleterious effect of vascular compromise, leading to abnormal skeletal blood flow and poor bone health. In addition, vascular diabetic complications are characterized by increased vascular calcification, decreased arterial dispensability, and vascular remodeling. These extensive alterations in vascular structure lead to impaired myogenic control and reduced nitric-oxide mediated vasodilation, compromising regulation of blood flow across almost all vascular beds and significantly restricting muscle blood flow in T1D. Vascular deficits in T1D may very well extend to bone, compromising bone blood flow control, and resulting in reduced blood flow to bone, thus negatively impacting bone health. Indeed, several animal and ex vivo human studies report that diabetes induced microvascular damage within bone is strongly correlated with diabetes disease severity and duration. In this review, we will discuss the contribution of diabetes-induced vascular deficits to bone microarchitecture and bone blood flow regulation, and review the potential contribution of vascular disease to skeletal fragility in T1D.